The Catumbela delta (SW Angola). Processes determining a history of changing asymmetry. (September 2018) - Dinis, P.A.; Huvi, J.; Callapez, P.M.
Abstract: It is presented an investigation on the morpho-sedimentary evolution of one of the largest sub-aerial delta protrusions in west Africa: the Catumbela delta. The planform geometry of this delta is characteristic of an asymmetric wave-dominated accumulation, strongly influenced by a north-directed longshore drift. Its post-glacial Holocene construction passed through morphological transformations linked with the relocation of the main fluvial channels and river mouths. Avulsion processes in the delta plain are responsible for an alternation between two major channel courses: one directed E-W and broadly coincident with today's path and the other placed to the north with a SSE-NNW direction. Delta growth started during a period of deceleration of sea-level rise and high rainfall (c.a. 7 ka BP) and was enhanced after the 4.5 ka. BP sea-level highstand. A deflected delta configuration was promoted by the c.a. 2–3 ka BP climatic crisis, when fluvial sediment supply was reduced and sediment bypassing limited to a minimum, forcing the channel to run parallel to the coastline. This configuration can be regarded as one of the finest worldwide examples of medium-size deflected deltas. The later updrift migration in the position of the river mouth was probably determined by an increase in fluvial supply driven by an upsurge in the seasonal rainfall in the drainage area and, in particular during the last 200 years of Portuguese occupation of the territory, changes in land-use. The updrift migration, however, was irregular, being punctuated by events of downdrift shifts and two channel courses with outlets several km apart may persist during wet periods. Highlights: Two main river courses recognized in the wave-dominated Catumbela delta. Morphology of the delta determined by relocations of the main fluvial channel. Geometry typical of deflected deltas during arid period (2–3 ka) of low discharge. Post-2 ka updrift migration of the outlet due to increase in fluvial sediment supply.